2022
DOI: 10.1532/hsf.4913
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Prolonged Mechanical Ventilation in Patients Undergoing Redo Valve Surgery

Abstract: Background: Prolonged mechanical ventilation (PMV) after cardiac surgery is associated with high morbidity and mortality. Patients following redo valve surgery possess many attributes that place them at risk for PMV, yet few studies particularly focused on them. The purpose of this study was to identify perioperative variables associated with PMV in redo valve surgery. Methods: A retrospective study, including 117 patients who underwent redo valve surgery from November 2017 to September 2021, was performed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The results are below than those reported in burns with ABSI with predicted mortality between 55 and 82%, which suggest prolonged mechanical ventilation for more than 21 days, difficult weaning, in addition to pneumonia and ventilator-induced lung injury. 5 The increase in mechanical power values during prone positioning is related to death, 23 in this research we found a significant reduction in mechanical power with mortality below that predicted by the specific ABSI index for burns.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The results are below than those reported in burns with ABSI with predicted mortality between 55 and 82%, which suggest prolonged mechanical ventilation for more than 21 days, difficult weaning, in addition to pneumonia and ventilator-induced lung injury. 5 The increase in mechanical power values during prone positioning is related to death, 23 in this research we found a significant reduction in mechanical power with mortality below that predicted by the specific ABSI index for burns.…”
Section: Discussionmentioning
confidence: 45%
“…3 ARDS can result from inhalation injury, and it becomes more serious when it is combined with SIRS generated by extensive and deep burns. 4 Mechanical ventilation is an essential support for severely burned patients 5 with the intention of ensuring sufficient hematosis (the conversion of venous into arterial blood, i.e. oxygenation and CO2 removal i.e.…”
Section: Introductionmentioning
confidence: 99%